2018
DOI: 10.1074/jbc.ra118.002018
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold attachment factor B suppresses HIV-1 infection of CD4+ T cells by preventing binding of RNA polymerase II to HIV-1's long terminal repeat

Abstract: The 5' end of the HIV, type 1 (HIV-1) long terminal repeat (LTR) promoter plays an essential role in driving viral transcription and productive infection. Multiple host and viral factors regulate LTR activity and modulate HIV-1 latency. Manipulation of the HIV-1 LTR provides a potential therapeutic strategy for combating HIV-1 persistence. In this study, we identified an RNA/DNA-binding protein, scaffold attachment factor B (SAFB1), as a host cell factor that represses HIV-1 transcription. We found that SAFB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Because the initiation and elongation of HIV-1 LTR-driven transcription can be assessed by quantifying transcripts of various lengths of HIV mRNA with PCR using specific primers (6163), we also examined the relative lengths of the PCR products and found that AHR knockdown in HEK293T cells significantly shortened the length of each PCR product, suggesting a blockade of both the initiation and the elongation of HIV-1 5ˊ-LTR-driven transcription (unpaired t test, P < 0.05 and P < 0.001, respectively) (Fig. 4D, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Because the initiation and elongation of HIV-1 LTR-driven transcription can be assessed by quantifying transcripts of various lengths of HIV mRNA with PCR using specific primers (6163), we also examined the relative lengths of the PCR products and found that AHR knockdown in HEK293T cells significantly shortened the length of each PCR product, suggesting a blockade of both the initiation and the elongation of HIV-1 5ˊ-LTR-driven transcription (unpaired t test, P < 0.05 and P < 0.001, respectively) (Fig. 4D, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…5B and C). To confirm that the observed correlation of RBMX expression and HIV-1 reactivation is not an artifact in a single cell line, we tested this in the HIV-1 latently infected Jurkat T-cell (C11 clone) which harbors an HIV-1 proviral DNA encoding green fluorescent protein (GFP) (13,(36)(37)(38). Similar to results obtained in ACH2 cells, the knockdown of endogenous RBMX in C11 cells with shRNAs promoted both basal (medium) and TNF-␣stimulated HIV-1 reactivation ( Fig.…”
Section: Fig 4 Rbmx Binds With and Maintains H3k9me3 Modification Formentioning
confidence: 99%
“…The initiation and elongation of HIV-LTR-driven transcription can be assessed by quantifying the production of various lengths of viral messenger RNAs with (RT-) PCR using specific primers (68,70). We found that MALAT1 knockout significantly decreased the production of initial viral message RNAs, but did not further decrease the production of elongated viral RNAs, indicating that the depletion of MALAT1 impaired the initiation of HIV-LTR-driven transcription, but not the elongation (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…The reversible silencing of LTR-driven transcription is critical for an integrated provirus to maintain viral latency (68,70,77–80). The promotion effect of MALAT1 on HIV-1 LTR-driven gene expression suggests a potential role for MALAT1 in reactivating HIV-1 from latency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation